A Multimethod Assessment of a New Customized Heat-Treated Nickel–Titanium Rotary File System - Silva, Emmanuel J. N. L. (2022)
Funding Information: Funding was provided by CENIMAT/i3N through national funds obtained through the FCT-Fundação para a Ciência e a Tecnologia, I.P., within the scope of Multiannual Financing of R&D Units, reference UIDB/50025/2020-2023, and is acknowledged by F.M.B.F. Fernanda Carvalho is acknowledged for running the DSC tests of the files. This study was also partly funded by the Fundação de Amparo à Pesquisa do Estado do Rio de Janeiro (FAPERJ), reference E-26/201.249/2021 and by the Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq), reference 403655/2021-8. Publisher Copyright: © 2022 by the authors.